3D Tissue Models as an Effective Tool for Studying Viruses and Vaccine Development - Lawko, Nathan; Plaskasovitis, Charlie; Stokes, Carling; Abelseth, Laila; Fraser, Ian; Sharma, Ruchi; Kirsch, Rebecca; Hasan, Misha; Abelseth, Emily; Willerth, Stephanie M. (Frontiers in Materials, 2021)
The recent SARS-CoV-2 outbreak has researchers working tirelessly to understand the virus’ pathogenesis and develop an effective vaccine. The urgent need for rapid development and deployment of such a vaccine has illustrated the limitations of current practices and it has highlighted the need for alternative models for early screening of such technologies. Traditional 2D cell culture does not accurately capture the effects of a physiologically relevant environment as they fail to promote appropriate cell-cell and cell-environment interactions. This inability to capture the intricacies of the in vivo microenvironment prevents 2D cell cultures from demonstrating the necessary properties of native tissues required for the standard infection mechanisms of the virus, thus contributing the high failure rate of drug discovery and vaccine development. 3D cell culture models can bridge the gap between conventional cell culture and in vivo models. Methods such as 3D bioprinting, spheroids, organoids, organ-on-chip platform, and rotating wall vessel bioreactors offer ways to produce physiologically relevant models by mimicking in vivo microarchitecture, chemical gradients, cell–cell interactions and cell–environment interactions. The field of viral biology currently uses 3D cell culture models to understand the interactions between viruses and host cells, which is crucial knowledge for vaccine development. In this review, we discuss how 3D cell culture models have been used to investigate disease pathologies for coronaviruses and other viruses such as Zika Virus, Hepatitis, and Influenza , and how they may apply to drug discovery and vaccine development.